1995
DOI: 10.2105/ajph.85.6.854
|View full text |Cite
|
Sign up to set email alerts
|

A preventive child health program: the effect of telephone and home visits by public health nurses.

Abstract: A randomized trial was conducted to determine if a public health nursing intervention consisting of telephone contacts or home visits affected the receipt of preventive health services by children eligible for the Early Periodic Screening, Diagnosis, and Treatment program. Each nursing intervention was applied using a protocol, and outcome data for 1654 case subjects were obtained from state-paid provider claims. However, the trial revealed no statistically significant differences between the study groups, nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The most promising impact of two or less nursing encounters has been its influence on client's use of other health care services (Bradley & Martin, 1994; Ghilarducci & McCool, 1993; Oda & Boyd, 1988; Zotti & Zahner, 1995). Other researchers have found no significant difference in health outcomes between control groups and clients who received one or two nursing contacts (Barkauskas, 1983; Oda, Heilbron, & Taylor, 1995; Stanwick, Moffat, Robitalle, Edmond, & Dok, 1982). Byrd (1997) described the customary single postpartum home visit as primarily a screening activity in which the PHN provides as much health and referral information as possible.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The most promising impact of two or less nursing encounters has been its influence on client's use of other health care services (Bradley & Martin, 1994; Ghilarducci & McCool, 1993; Oda & Boyd, 1988; Zotti & Zahner, 1995). Other researchers have found no significant difference in health outcomes between control groups and clients who received one or two nursing contacts (Barkauskas, 1983; Oda, Heilbron, & Taylor, 1995; Stanwick, Moffat, Robitalle, Edmond, & Dok, 1982). Byrd (1997) described the customary single postpartum home visit as primarily a screening activity in which the PHN provides as much health and referral information as possible.…”
Section: Literature Reviewmentioning
confidence: 96%
“…As clinicians we might have anticipated that the physical presence and educational and supportive input from a home visitor alone was unlikely to benefit these disadvantaged mothers in the long term. Two large ( and 1654) randomized controlled trials with n ϭ 2235 high-risk families demonstrated that home visitations with social support and education only had no discernable advantage for these mothers or their infants (Oda, Heilbron, & Taylor, 1995;Villar et al, 1992).…”
Section: Overview Of Past Evaluations and Follow-upmentioning
confidence: 99%
“…The Use of EPSDT Services by Medicaid Children purpose was to motivate parents to seek EPSDT visits for their children (Oda, Heilbron, and Taylor 1995;Selby-Harrington et al 1995).…”
Section: Previous Researchmentioning
confidence: 99%